Structure engineering of solution-processed precursor films for low temperature fabrication of CuIn(S, Se)2 solar cells. (15th May 2021) - Yu, Shaotang; Jiang, Jingjing; Han, Shuaiqi; Hao, Shasha; Zhu, Qiang; Gong, Yuancai; Yan, Weibo; Huang, Wei; Xin, Hao
Graphical abstract: Highlights: Structure engineering of solution-processed precursor films enables fabrication of highly efficient CISSe solar cells under low temperature selenization. Extra layer of Cu2 S is inserted into precursor film for forming enough Cu2−x Se to facilitate grain growth at low temperature. Characterizations show that new structure improves the quality of CISSe absorber. An efficiency of 6.13% is achieved from the new structure which is only 3.83% for normal structure. Abstract: Fabrication of flexible Cu(In, Ga)(S, Se)2 (CIGS) thin-film solar cell via precursor solution is a promising approach due to its perfect compatibility with roll-to-roll production. So far, polyimide (PI) is the most suitable substrate for flexible CIGS solar cell because of many advantages such as low cost, light weight, good insulativity and free of metallic impurities. However, PI has not been used in solution-processed approach because PI cannot tolerate the annealing process (selenization) at high temperature (≥550 °C) which is normally required for most of highly efficient CIGS solar cells fabricated via precursor solution. Here, we report low temperature (450 °C) fabrication of CuIn(S, Se)2 (CISSe) absorber by carefully engineering the structure of solution-processed precursor film. By adding extra Cu2 S into solution-processed CuInS2 (CIS) precursor films through structure engineering of Mo/In2 S3 /Cu2 S (bilayer), Mo/CIS/Cu2 S/(CIS/Cu2 S)3 /CIS (multilayer), enough Cu2−x Se is formed in low temperature selenization which facilitates the formation process of CISSe absorber. Characterizations using XRD, Raman, SEM and EDX show that absorbers fabricated from precursor films with new structures favor the sufficient selenization, resulting in much better morphology and higher photovoltaic performance than the absorber fabricated from precursor film with normal structure of Mo/CIS (single layer). After preliminary optimization, efficiencies of 5.01% and 6.13% have been achieved in CISSe solar cells fabricated from precursor films with new structures which is only 3.83% from normal structure. Our results demonstrate the feasibility of fabricating efficient chalcopyrite solar cells via precursor solution in low temperature selenization.